2019
DOI: 10.1039/c9cc05413h
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia-supported rhenium oxide as an efficient catalyst for the synthesis of biomass-based adipic acid ester

Abstract: ZrO2-Supported ReOx is an efficient catalyst for the synthesis of adipic acid ester from cellulose-derived glucaric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…Rhenium (Re) is not a very common element in heterogeneous catalysis, and it is only sometimes considered to be a noble metal. An example of its application in heterogeneous catalysis is the deoxydehydration (DODH) of biomass-derived polyols to produce adipic acid over ReO x supported on ZrO 2 [ 126 ]. There has, however, recently been a handful of reports where Re is studied as a promoter in Ni-based catalysts for methanation.…”
Section: Promotion With Noble Metalsmentioning
confidence: 99%
“…Rhenium (Re) is not a very common element in heterogeneous catalysis, and it is only sometimes considered to be a noble metal. An example of its application in heterogeneous catalysis is the deoxydehydration (DODH) of biomass-derived polyols to produce adipic acid over ReO x supported on ZrO 2 [ 126 ]. There has, however, recently been a handful of reports where Re is studied as a promoter in Ni-based catalysts for methanation.…”
Section: Promotion With Noble Metalsmentioning
confidence: 99%
“…Another application of these oxides deals with heterogeneous catalysis either as catalysts or as support. [6][7][8][9][10] As catalyst, because of the presence of Lewis and Brønsted acid sites, zirconia is mainly used in its sulfated formed (SO 4 /ZrO 2 ). 11,12 For example, sulfated ZrO 2 exhibits high activity for alkane isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…93 %. [37] It was found that changing the support had as ignificant effect on the reducibility of the ReO x species,w ith ZrO 2 providing favorable weak interactions with ReO x ,a llowing the reactiont ob ec onducted under relatively mild conditions (140 8C). When ReO x -Pd/CeO 2 was combined with Pd/C for subsequent hydrogenation of the alkenyl products to give the corresponding adipic acid ester in 82 %y ield.…”
Section: Heterogeneous Rhenium Catalystsmentioning
confidence: 99%
“…Similar to the homogeneous system reported by Toste and co‐workers, Deng and Wang have shown that zirconia supported rhenium oxide, ReO x /ZrO 2 , catalyzes the DODH of d ‐glucaric acid to the corresponding alkenyl dibutyl adipate esters using n ‐butanol as reductant to give a combined yield of 93 % . It was found that changing the support had a significant effect on the reducibility of the ReO x species, with ZrO 2 providing favorable weak interactions with ReO x , allowing the reaction to be conducted under relatively mild conditions (140 °C).…”
Section: Heterogeneous Rhenium Catalystsmentioning
confidence: 99%